Pentaband Slotted Microstrip Patch Antenna for Wireless Applications - Chauhan, Anukriti; Singh, BK; Gangwar, RPS; Singh Chauhan, Shakti (International Journal of Computer Sciences and Engineering, 2014)
A pentaband slotted microstrip patch antenna for wireless applications operating in the frequency range of 2-25GHz is designed and simulated. Four pentagonal slots in radiating patch and a square slot in ground plane are introduced to get improved antenna parameters. The proposed antenna resonated at five resonant frequencies 11.373GHz with return loss -42.63dB, 16.85GHz with return loss -13.52dB, 18.67GHz with return loss -11.75dB, 21.56GHz with return loss -16.72dB and 24.28GHz with return loss -45.26dB resulting in five frequency bands. Transmission line model is used to calculate initial dimensions and IE3D simulation software based on method of moments is used for optimization of proposed antenna. The simple structure of proposed antenna makes its fabrication easy and multiband operation makes it suitable for X-band, Ku-band and K-band applications.